Evaluation of basil extract ( Ocimum basilicum L.) on oxidative, anti-genotoxic and anti-inflammatory effects in human leukocytes cell cultures exposed to challenging agents - Camila Martins Güez; Raul Oliveira de Souza; Paula Fischer; Maria Fernanda de Moura Leão; Jonathaline Apollo Duarte; Aline Augusti Boligon; Margareth Linde Athayde; Luísa Zuravski; Luís Flávio Souza de Oliveira; Michel Mansur Machado (Universidade de São Paulo, 2017)
ABSTRACT Ocimum is one of the most important genera of the Lamiaceae family. Several studies about basil and its popular use reveal many characteristics of the herb, including its use as antioxidant, anti-aging, anti-inflammatory, anti-carcinogenic, anti-microbial, and cardiovascular agents, among others. In this paper, we evaluated genotoxic, oxidative, and anti-inflammatory parameters from the extract of Ocimum basilicum in different concentrations, using human leukocytes cultures exposed to challenging agents. Our results confirm that the O. basilicum extract acts as an antioxidant and effectively reverts or subjugates the effects of high oxidizing agents such as hydrogen peroxide. These actions are attributed to its composition, which is rich in polyphenols and flavonoids as well as compounds such as rosmarinic acid, all of which have well-known antioxidant activity. We also show that our basil extract presents anti-inflammatory properties, the mechanism of which is a composed interaction between the inhibition of pro-inflammatory mediator and the stimulation of anti-inflammatory cytokines. Although pharmacodynamics studies are necessary to evaluate the activities in vivo, our results demonstrated that basil could act as an antioxidant and anti-inflammatory and a possible alternative for medicinal treatment.